Adolescents' experiences of a school-based health promotion intervention in socioeconomically advantaged and disadvantaged areas in Sweden: a qualitative process evaluation study - Lisette Farias; Gisela Nyberg; Björg Helgadóttir; Susanne Andermo (BMC, 2023)
Abstract Background Adolescence is a transition period in which positive experiences of physical activity have the potential to last into later adulthood. These experiences are influenced by socioeconomic determinants, leading to health inequalities. This study aims to explore adolescents' experiences and participation in a multi-component school-based intervention in schools located in socioeconomically advantaged and disadvantaged areas in Sweden. Methods A qualitative design was used to evaluate how participants experienced the intervention. The intervention was a multi-component school-based intervention. It was conducted in six schools (four control and two intervention schools) with a total of 193 students and lasted one school year. It was teacher-led and consisted of three 60-minute group sessions per week: varied physical activities, homework support with activity breaks, and walks while listening to audiobooks. In total, 23 participant observations were conducted over eight months and 27 students participated in focus groups. A content analysis was conducted. Results The results describe a main category 'Engaging in activities depending on socioeconomic status' and three generic categories: 1. Variations in participation in PA together with classmates and teachers; 2. Variations in engagement in PA after school; and 3. Differences in time and place allocated to do homework and listen to audiobooks. These categories illustrate how participants looked forward to the physical activities but used the time spent during the walks and homework support differently depending on how busy they were after school. Frequently, those who were busiest after school were also those from the advantaged area, and those who had little to do after school were from the disadvantaged area. Conclusion Socioeconomic factors influence participants' possibilities to engage in the intervention activities as well as how they use their time in the activities. This study showed that it is crucial to support adolescents' participation in physical activities by providing structure and engaging well-known teachers in the activities, especially in schools located in disadvantaged areas.